New Trends of Islamic Resurgence in Contemporary Malaysia: Sufi-Revivalism, Messianism, and Economic Activism - Hamid, A. Fauzi A. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
This paper, based on research entitled